Contact patterns during the COVID-19 pandemic: findings from British Columbia, Canada. (March 2022) - Adu, P.; Binka, M.; Iyaniwura, S.; Ringa, N.; Irvine, M.; Otterstatter, M.; Janjua, N.
Abstract : Purpose: Interpersonal interaction between infectious and uninfected individuals facilitates the spread of COVID-19. Physical distancing measures could prevent COVID-19 transmission by reducing the contacts among individuals in the population. In this study, we describe contact rates of residents of British Columbia, Canada to assess the impact of COVID-19 related physical distancing measures in the province. Methods & Materials: We used data from the BC COVID-19 Population Mixing Patterns survey (BC-Mix) to investigate the contact patterns of residents of British Columbia from September 2020 to July 12, 2021. The BC-Mix is an ongoing repeated online survey with approximately 60, 000 participants. Survey respondents provided the number of close contacts made in a single day in response to the question "How many people did you have in-person contact with between 5 am yesterday and 5am today?" In-person contact was defined as "face-to-face two-way conversation with three or more words, or physical skin-to-skin contact such as a handshakes, hugs, kisses and contact sports". Survey weights were applied in the estimation of overall contact rates and contact rates stratified by age, sex and health region. Results: A total of 31, 696 respondents were eligible for analysis. Overall average daily contacts decreased by about 28% in response to the physical distancing measures that went into effect on November 19, 2020 (from an average of 6.42 contacts per person prior to this date to 4.62 contacts per person after this date). From September 2020 to February 2021, the average number of daily contacts were higher among female respondents compared to male respondents. However, no notable difference in the average number of daily contact rates was observed between male and female respondents in subsequent weeks. Over the study period, younger age groups (< 55 years) reported higher daily contact overall than older age groups (≥ 55years years). There was also a marked difference in contact rates by health regions over the study period. Conclusion: Contact patterns in British Columbia varied between September 2020 and July 2021, with a marked decline in average daily contacts noted immediately following the introduction of stricter physical distancing measures in November 2020.